Pengaruh pemilihan staf, comprehensive training, strategi eksploitasi, strategi eksplorasi terhadap kinerja keuangan, yang dimediasi oleh praktik sumber daya manusia - Dahono, Trigonggo Simbar; Bariz Falah, Teuku Daffa; Tanuwijaya, Justine (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study aims to see how the relationship between Pemilihan Stafing and HR competency development through Comprehensive Training towards the exploration and exploitation process as well as the management and approach taken by SDM towards optimal and effective Kinerja Keuangan. This research uses quantitative research methods. The population in this study were all employees from various industries in Indonesia. This study consisted of 200 respondents. The sampling technique in this study used a saturated sampling technique, where the entire population was sampled. The results in this study indicate that the increase in the company's Kinerja Keuangan is strongly influenced by direct Praktik SDM and exploitation strategies through Praktik SDM. Where to strengthen and improve the practice of SDM itself is also strongly influenced by strengthening and improving exploitation strategies. And to strengthen and improve the Strategi Eks